Environmental services and water use in South Asia: evidences from Indo-Gangetic basins - Xenarios, Stefanos; Sharma, Bharat R.; Singh, A. (2010)
The significance of environmental services related with irrigation is increasingly acknowledged as a critical factor for agricultural productivity in South Asia. However, little is known about farmers' willingness to contribute for the preservation of these services. To this aim, we conduct a stated preference approach for the elicitation of farmers preferences towards the economic value attributed to environmental services related with agricultural water use. The research is based on results from an extensive survey in selected clusters of India, Pakistan and Nepal. The case studies are situated along Indo-Gangetic basins due to the presence of more evident environmental problem linked with irrigation. The findings present a highly agreeable stance of Indian and Nepalese farmers towards the contribution to the environmental services while the majority of Pakistani is opposed to such a contribution. However, they all agree on the type of the assessment approach. The association of the economic assessment with key wealth indicators and socio-demographic elements depicts the high significance of household size.